PERFORMANCE ANALYSIS OF PBB-P2 TAX COLLECTION IN KEJAYAN URBAN VILLAGE, PASURUAN DISTRICT - Agnesti, Sitha Iasha (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2024)
Performance Analysis is an evaluation activity carried out by government and private agencies that aims to measure the success and failure of the implementation of tasks and functions. Apparatus performance measurement can help measure the success of apparatus performance in carrying out their duties and functions, so as to provide objective information about the implementation of government activities. In this study, using a qualitative descriptive approach using data collection techniques of interviews, observation and documentation. This study uses the theory of Mathis N Jacson (2006) to analyze the performance of PBB-P2 tax collection in Kejayan village. There are 5 Indicators namely output quality, output quantity, output timeliness, attendance at work and cooperative attitude. The results of the study stated that PBB-P2 tax collection experienced many external obstacles which were included in the indicators of output quality and cooperative attitude of PBB-P2 tax collection. Then in this study, the authors provide strategies to minimize these obstacles.